New distributions for 24 species of Calceolaria (Calceolariaceae) in Peru and first record of Calceolaria perfoliata - Puppo, Pamela (2010)
Twenty four species of Calceolaria are recorded for the first time for 15 departments of Peru and the presence of C. perfoliata is reported in this country. In addition, a list with the 123 species present in Peru is included along with their current geographical distribution. A general analysis of the genus diversity per department is done.